New challenges in the biomedical science: biobanking problems and solutions - Gudlevičienė, Živilė; Chvatovič, Genovefa (Acta medica Lituanica, 2014)
Background. A huge progress has been recently made in the field of biomedical research and personalized medicine. Despite the advances of biobanking, significant limitations remain that are restricting the impact of researches. The major issues include the need to increase the quality and standardization of biospecimens and to maintain public trust. In general, it is named as harmonization of biobanking activities. The purpose of this article is to overview the current situation in biobanking issues and discuss about the possible solutions of these problems in Lithuania. The first steps in biobanking activities were made in the Institute of Oncology, Vilnius University (IOVU); several methods of DNA extraction from peripheral blood were tested and compared. Materials and methods. During the experiment, four manual DNA extractions and one automated DNA purification method to determine the efficiency of each method in terms of the purity and yields of DNA extracted from blood samples were tested. DNA from patient’s blood remaining after a routine blood test was purified. Results. Two of the four manual extraction methods produced good yields of DNA (from 57 to 126 µg/ml), the other two were of poor quality (from 8 to 47 µg/ml). In the same samples automatically isolated DNA concentrations ranged from 15 to 95 µg/ml. Conclusions. The first steps for biobanking activities, SOPs creation and process harmonization were made in IOVU. Finally, after appreciation of the general situation the main threats in Lithuania could be proposed. The general working plan and strategy for biobanking in Lithuania, according to international rules and national needs, must be applied.
Keywords: biobanking; harmonization; SOPs; DNA extraction; DNA long-term storage